2022
DOI: 10.3390/molecules27217144
|View full text |Cite
|
Sign up to set email alerts
|

Dual-State Emission of 2-(Butylamino)Cinchomeronic Dinitrile Derivatives

Abstract: New representatives of 2-(butylamino)cinchomeronic dinitrile derivatives were synthesized as promising fluorophores showing dual-state emission. To characterize the influence of the length (from methyl to butyl) and the structure (both linear and branched) of the alkyl substituent at the amino nitrogen atom, the spectral fluorescence properties of all synthesized compounds were carefully studied both in solution and in solid state. The highest photoluminescence quantum yield values of 63% were noted for soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For secondary amines, a side reaction of halogen substitution for the corresponding amine was observed. 45 46 Among the butoxides, potassium tert -butoxide was found to give the best results. It was found that the optimal temperature for the best yield is 25–35 °C.…”
Section: Table 1 Screening Of Reaction Conditions For T...mentioning
confidence: 99%
“…For secondary amines, a side reaction of halogen substitution for the corresponding amine was observed. 45 46 Among the butoxides, potassium tert -butoxide was found to give the best results. It was found that the optimal temperature for the best yield is 25–35 °C.…”
Section: Table 1 Screening Of Reaction Conditions For T...mentioning
confidence: 99%
“…The mobile halogen atom and two reactive cyano groups will allow a facile modification of the acceptor unit of chromophores by the introduction of the desired moieties. [51][52][53][54][55][56][57][58][59]…”
Section: Introductionmentioning
confidence: 99%